Contradictions of democracy in a workers' cooperative - Varman, Rahul; Chakrabarti, Manali (2004)
Organizational democracy has become a key issue in current change-management programmes, such as restructuring, total quality management and Enterprise Resource Planning, and there has been a persistent quest for a post-Fordist model in recent times. The article emphasizes the need to study democratic processes per se, given that democracy faces significant odds vis-a-vis the larger context, even in those organizations that have been expressly initiated for democratic functioning. The contradictions with the context inevitably manifest themselves inside the organization as well. The present study makes a case for understanding organizational democracy as an evolving reality, based on participant observation of democratic functioning within a workers' cooperative over seven years. - Reproduced.
Keywords: Organizations; Cooperatives; Workers; Workers participation